y=10-0.667*(15-1.5y-2.5z)-1.667z

Simple and best practice solution for y=10-0.667*(15-1.5y-2.5z)-1.667z equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y=10-0.667*(15-1.5y-2.5z)-1.667z equation:


Simplifying
y = 10 + -0.667(15 + -1.5y + -2.5z) + -1.667z
y = 10 + (15 * -0.667 + -1.5y * -0.667 + -2.5z * -0.667) + -1.667z
y = 10 + (-10.005 + 1.0005y + 1.6675z) + -1.667z

Combine like terms: 10 + -10.005 = -0.005
y = -0.005 + 1.0005y + 1.6675z + -1.667z

Combine like terms: 1.6675z + -1.667z = 0.0005z
y = -0.005 + 1.0005y + 0.0005z

Solving
y = -0.005 + 1.0005y + 0.0005z

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-1.0005y' to each side of the equation.
y + -1.0005y = -0.005 + 1.0005y + -1.0005y + 0.0005z

Combine like terms: y + -1.0005y = -0.0005y
-0.0005y = -0.005 + 1.0005y + -1.0005y + 0.0005z

Combine like terms: 1.0005y + -1.0005y = 0.0000
-0.0005y = -0.005 + 0.0000 + 0.0005z
-0.0005y = -0.005 + 0.0005z

Divide each side by '-0.0005'.
y = 10 + -1z

Simplifying
y = 10 + -1z

See similar equations:

| 30=2A+3B+5C | | -12.5+5=x | | w^2+16w^2=c | | 10=2A+3B+5C | | 37x=56+89 | | 54x+18x-12-8x=100 | | 34-5x=7-8x | | 6=2x+20 | | 10x-20=9x+9 | | 24x=72*72-48*48 | | 60x=53*53-37*37 | | 12x=34*34-26*26 | | 23x=68*68-45*45 | | 2x+18=45 | | 12x=50*50-38*38 | | (3a+b)2= | | 6cn-2cn= | | 4x+18x+32=54 | | -2y=1-4x | | 3x=1-4y | | (3x-8)(6x^2-14)=0 | | 6x-9=2m+47 | | 27.8x=2880 | | 5(7+x)-4=-x+1 | | 3[8c+5]= | | y=ln(4x^2) | | p(p-4)-21=0 | | 2x^2+2y^2+12x+12y+20=0 | | 2x*2+2y*2+12x+12y+20=0 | | 2x=sqrt(2x+1) | | sqrt(5x+1)+2=2x | | x+sqrt(x^2-3x+3)=sqrt(x^2+2x+10)+1 |

Equations solver categories